The prevalence of frailty and its associated factors among Iranian hospitalized older adults - Masoumeh Shohani; Iman Mohammadi; Hossein Seidkhani; Sara Mohamadnejad (Kashan University of Medical Sciences, 2022)
Background: As the population ages, the impact of age-related diseases on health is becoming more apparent. Frailty is one of the most important issues faced by older adults. Objectives: This study aimed to determine the prevalence of frailty and the factors affecting it among older adults admitted to teaching hospitals in Ilam in 2020. Methods: This cross-sectional study was performed on 270 older adults admitted to teaching hospitals in Ilam. Participants were selected through consecutive sampling. Data were collected using the Tilburg Frailty Indicator and analyzed by the Chi-square test and logistic regression analysis. Results: The mean age of the older adults participating in the study was 71.97 ± 8.42 years. Overall, 18.1% of older adults were frail, and frailty was significantly associated with having a chronic disease, being accompanied by a close relative, hospitalization, age, sex, marital status, and education level (P < 0.05). The most important predictors of frailty in older adults were age, sex, history of stroke, and being accompanied by a close relative (P < 0.05). Conclusion: About one-fifth of the older adults participating in this study were frail. The prevalence of frailty was higher among women, those with chronic diseases or a history of stroke, single people, and those with low education levels. Therefore, these people need special attention.